2022
DOI: 10.1002/bio.4324
|View full text |Cite
|
Sign up to set email alerts
|

Colour‐switchable and photoluminescent polyvinyl chloride for multifunctional smart applications

Abstract: Recycled polyvinyl chloride (PVC) waste was used to prepare transparent materials with long-lasting phosphorescence, photochromic activity, hydrophobicity, strong optical transmission, ultraviolet (UV) light protection, and stiffness. Lanthanideactivated aluminate (LaA) microparticles were prepared using a high temperature solid-state procedure, and were subjected to top-down grinding technology to produce lanthanide-aluminate nanoparticles (LaAN). Laminated PVC bottles were shredded into a transparent plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Fibres with a high NLA ratio (>0.9%) were observed for their slow reversibility after turning off the UV lamp, indicating extended afterglow. Figure 5 The fluorescence of NLA has been shown to occur at two different wavelengths, one strongly green at a very long wavelength and the other weakly blue at a relatively short one [24,38]. Figure 6 displays PGLS 5 luminescence spectra as a function of time.…”
Section: Luminescence Analysismentioning
confidence: 99%
“…Fibres with a high NLA ratio (>0.9%) were observed for their slow reversibility after turning off the UV lamp, indicating extended afterglow. Figure 5 The fluorescence of NLA has been shown to occur at two different wavelengths, one strongly green at a very long wavelength and the other weakly blue at a relatively short one [24,38]. Figure 6 displays PGLS 5 luminescence spectra as a function of time.…”
Section: Luminescence Analysismentioning
confidence: 99%
“…[7,8] Due to their exceptional brightness, great recyclability, and nonradioactivity, long-persistent photoluminescent rare-earth activated aluminate nanoparticles (REANPs) have been identified as essential phosphors. [3,6,9] Technologies, including lithography, sol-gel, and chemical etching, have been used to create superhydrophobic materials. These approaches, however, have revealed challenges such as complicated procedures, time-consuming processing, and expensive instrumentation.…”
Section: Photochromic Inks and Smart Packaging Are Examples Of The Va...mentioning
confidence: 99%
“…[ 2 ] Fluorescence is light emission that stops when the radiation source is switched off, whereas phosphorescence is afterglow light emission with durations from a fraction of second to 1 h after the radiation source is switched off. [ 3–5 ] For phosphorescence to endure for an extended time period, crystals and traps are the main components in phosphors. Light absorption is a defining feature of crystals, and the energy they release can be captured in traps.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline earth aluminates are advantageous since they are non-toxic and non-radioactive. Because of their photochromic and durable phosphorescence properties, the AEA has been favored for a wide variety of products. , It has been observed that the photochromic and long-lived phosphorescence characteristics of a certain bulk material change when the concentration of AEA changes. As a result, the physical inclusion of AEAs (SrAl 2 O 4 :Eu 2+ ,Dy 3+ ) in a glass material introduces a new advance for the development of colorless smart glasses with persistent phosphorescence, fluorescence photochromism, robust surface, energy-saving character, and low cost .…”
Section: Introductionmentioning
confidence: 99%